Configuration Design and Kinematics Analysis of a New Type of a Quadruped Robot Leg Mechanism - Liu Yuntong; Li Xiaodan; Wang Xiaolei (Jixie chuandong)
Aiming at the low bearing capacity of the 3R series mechanical leg configuration, the leg configuration is improved, and two 3-DOF parallel leg configurations of 2R1T are proposed. A virtual prototype is built by Adams software with the same main structural dimensions, the same constraints and drives are added, a leg configuration is selected according to the comparison of the force of the linear actuator during loading, and the overall prototype design is completed. The leg coordinate system is established, the kinematics of the leg structure is analyzed by the vector method, the virtual prototype built by Adams software is used for simulation verification, the error between the theoretical value and the simulation value is small, and the correctness of kinematics is verified, which lays a foundation for further research and analysis.